Leisure and social occupational choice within nursing home facilities in Ireland: Residents perspectives - Jenna Keane; Ciara Ryan; Ruth Usher (Scandinavian Journal of Occupational Therapy)
Background National standards for nursing homes in Ireland require that residents are offered a choice of recreational and stimulating activities to meet their needs and preferences.Aims/Objectives To investigate residents’ perceptions of leisure and social occupational choice in nursing homes in Ireland to determine if occupational choice is facilitated.Materials and method Qualitative-descriptive design – nursing home residents completed two semi-structured interviews that explored their experiences of leisure and social occupational engagement.Results Two overarching themes with six associated sub-themes emerged. From residents’ perspectives, social and leisure occupational choice was dependent on: Environmental factors (nursing homes’ Cultural, Social, Physical, and Temporal Environments) and Personal factors (residents’ Health Status and Personal Attitudes).Conclusion The cultural environment had the most significant influence on residents’ leisure and social occupational choice, highlighting the importance of person-centred care within nursing homes, to promote occupational choice. Resident’s health status was also identified as a contributing factor.Significance Occupational therapists could play a critical role in supporting the leisure and social occupational choices of nursing home residents by developing residents’ skills, educating staff and adapting tasks and the environment to limit/reduce occupational deprivation.